Anti-inflammatory compounds from the mangrove endophytic fungus Amorosia sp. SCSIO 41026 - Ren, Xue; Chen, Chunmei; Ye, Yuxiu; Xu, Ziying; Zhao, Qingliang; Luo, Xiaowei; Liu, Yonghong; Guo, Peng (Frontiers in Microbiology, 2022)
Three new chlorinated compounds, including two propenylphenol derivatives, chlorophenol A and B (1 and 2), and one benzofuran derivative, chlorophenol C (3), together with 16 known compounds, were isolated from the mangrove endophytic fungus Amorosia sp. SCSIO 41026. 7-Chloro-3,4-dihydro-6,8-dihydroxy-3-methylisocoumarine (4) and 2,4-dichloro-3-hydroxy-5-methoxy-toluene (5) were obtained as new natural products. Their structures were elucidated by physicochemical properties and extensive spectroscopic analysis. Compounds 1, 4, 7, 9, 13, 15, 16, and 19 possessed inhibitory effects against the excessive production of nitric oxide (NO) and pro-inflammatory cytokines in lipopolysaccharide (LPS)-challenged RAW264.7 macrophages without obvious cytotoxicity. Moreover, 5-chloro-6-hydroxymellein (13) further alleviated the pathological lung injury of LPS-administrated mice and protected RAW264.7 macrophages against LPS-induced inflammation through PI3K/AKT pathway in vivo. Our research laid the foundation for the application of compound 13 as a potential anti-inflammatory candidate.